DSM-IV-defined anxiety disorder symptoms in a middle-childhood-aged group of Malaysian children using the Spence Children’s Anxiety Scale = Sintomas de transtorno de ansiedade definidos conforme o DSM-IV em um grupo de crianças Malaias na terceira infância segundo a escala de ansiedade infantil de spence - Atefeh, Ahmadi; Mohamed Sharif, Mustaffa; Amirmudin, Bin Udin; Ali Akbar, Haghdoust (Sociedade de Psiquiatria do Rio Grande do Sul, 2016)
Introduction: Pediatric anxiety disorders are the most common mental health disorders in the middle-childhood age group. The purpose of this study is to assess anxiety disorder symptoms, as defined by the Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV), in a large community sample of low socioeconomic level rural children and to investigate some of the psychometric properties (internal consistency, construct and convergent validity and items rated as often or always experienced) of the Malay version of the Spence Children’s Anxiety Scale-Child version (SCAS-C). Method: Six hundred children aged 9-11 and 424 of their parents completely answered the child or parent versions of the SCAS. Results: Results indicated that the internal reliability of subscales were moderate to adequate. Significant correlations between child and parent reports supported the measure’s concurrent validity. Additionally, anxiety levels in this Malaysian sample were lower than among South-African children and higher than among their Western peers. There were both similarities and differences between symptom items reported as often or always experienced by Malaysian students and by children from other cultures. Confirmatory factor analysis provided evidence of the existence of five inter-correlated factors for anxiety disorders based on SCAS-C. Conclusion: Although some of the instrument’s psychometric properties deviated from those observed in some other countries, it nevertheless appears to be useful for assessing childhood anxiety symptoms in this country.